Analysis of the Relationship Between Parenting Patterns and Supplementary Feeding on Stunting Incidence in Gedungboyountung Village - Siti Sholikha; Husnul Muthoharoh; Dellamitha Arifiah Muslim; Hibatun Mubarokah El Fitri (Universitas Muhammadiyah Sidoarjo, 2025)
Stunting is a persistent public health problem in Indonesia, particularly in rural communities, and is influenced by caregiving practices and dietary patterns. This study aimed to analyze the association between parenting practices, supplementary feeding (PMT), and the incidence of stunting among children aged 6–59 months in Gedungboyountung Village. A cross-sectional analytic design was conducted from June to August 2025 with 60 respondents selected through purposive sampling. Parenting and feeding practices were assessed using structured questionnaires, while stunting was determined based on height-for-age z-scores. Data were analyzed using the Chi-square test. The findings showed that 8.3% (5 children) were stunted. A significant association was observed between parenting practices and stunting (p = 0.028), indicating that children raised with poor parenting were more likely to be stunted. Supplementary feeding was also significantly associated with stunting (p = 0.014), with inappropriate or low-quality feeding practices increasing the risk of growth faltering. These results suggest that stunting in rural areas is strongly linked to behavioral and caregiving factors, especially the adequacy of food provision and the quality of parenting. Strengthening community-based health education programs to improve parenting skills and ensure appropriate supplementary feeding may serve as effective strategies to reduce stunting prevalence. Further studies with larger sample sizes and longitudinal approaches are recommended to confirm these findings and to explore additional determinants such as socioeconomic conditions, maternal education, and sanitation.